Analysis and Load Rating of Corrugated Steel Arch Culverts. Issue 3 (16th September 2019) - Xu, Chao; Peiris, Abheetha; Harik, Issam
ABSTRACT: Culverts are typically used as short span bridge substitutes for spans less 50 ft (15 m). The corrugated metal arch culvert (CMAC) is one of the most popular types, which is frequently installed under highways, airport pavements and railroad tracks. For the purpose of validating the service conditions of CMAC, a load rating method is developed in this study based on AASHTO Manual for Bridge Evaluation. The rating factors (RFs) for culverts are derived to verify the capacity of the culverts to carry current standard truck loads. In order to carry out the load rating, a finite element model of the CMAC is developed for analysing the axial thrust of the culvert wall when subjected to static and dynamic moving truck loads. A method to calculate the CMAC wall thrust capacity is derived by summarizing existing capacity calculation approaches for arch culvert and corrugated metal plates.